ANALISIS PENGARUH PENDEKATAN TOP DOWN, MARKET TIMING ABILITY, STOCK SELECTION SKILL TERHADAP KINERJA KEUANGAN PERUSAHAAN PROPERTI DI INDONESIA PERIODE 2011 – 2014 - Nurani Utami (Jurnal Akuntansi dan Keuangan, 2019)
A decision on an investment is generally based on a consideration of the magnitude of the expected return investor and the risk that expected to be encountered. Hence require more stock performance assessment indicators such as The Top down approach, Market timing ability and Stock Selection skill. The purpose of this research was to analyze the effect of the level of the Top down approach, Market timing ability and Stock Selection skill on the performance of property stocks. The data used in this research is data of property stocks listed on the Indonesian stock exchange of 24 property stocks 2011-2014 period using SPSS software version 21. The results of this study indicate that partial of top-down approach has not a significant effect on the financial performance of property while market timing ability and stock selection skill has significant to the financial performance of property.